Evaluation of Interleukin-6 Levels in Patients with Type 2 Diabetes Mellitus - Dutta, Shantanu; Haque, Mahmudul; Islam, MD Hafizul; Chowdhury, Pratik; Mushtaree, Sheikh Shafatin; Chowdhury, Nasreen (IAHS Medical Journal, 2024)
Background: It has been suggested that inflammatory processes play an important role in the pathogenesis of type 2 diabetes. Individuals who develop type 2 diabetes show signs of low-grade inflammation years before disease onset. This low-grade inflammation has been assumed to be implicated in the pathogenetic mechanisms that cause type 2 Diabetes Mellitus. Inflammatory mediators such as the IL-6 family of cytokines have been proposed to be involved in the events that lead to type 2 diabetes. IL-6 has immunoregulatory actions been proposed to affect glucose homeostasis and metabolism directly and indirectly by action on skeletal muscle cells, adipocytes, hepatocytes, pancreatic b-cells and neuroendocrine cells. Many studies have suggested the role of IL-6 in the pathogenesis of type 2 diabetes mellitus. However, no references have been observed in Bangladesh regarding IL-6 and its association with type 2 diabetes mellitus. It thus may highlight the importance of low-grade inflammation in the pathophysiology of type 2 diabetes mellitus. The purpose of this study was to evaluate type 2 diabetes patients' levels of interleukin-6. Materials and methods: A hospital-based cross-sectional observational study was carried out in the Department of Biochemistry Chittagong Medical College, Department of Endocrinology of Chittagong Medical College Hospital and Chattogram Diabetic Hospital. One hundred (100) type 2 diabetes mellitus patient was included in the study by nonprobability consecutive sampling. Important variables in this study were serum IL-6, BMI, waist circumference and duration of Diabetes Mellitus. Results: The mean serum IL-6 level was 10.08±0.39 pg/ml in patients with type 2 Diabetes Mellitus. Serum IL-6 was positively correlated (r 0.33, p <0.01) with waist circumference and duration of diabetes mellitus (r 0.26, p <0.05). The mean IL-6 was significantly different between BMI groups (F (2,97) =5.39, p=0.006) and was higher in the obese group (10.52±4.00) compared to the overweight and normal BMI (6.78±1.95) and overweight (8.08±3.15) group. Conclusion: It can be concluded that type 2 diabetes mellitus patients had increased serum levels of IL-6. It can give an insight into the possible role of sub clinical inflammation among patients with type 2 Diabetes Mellitus. IAHS Medical Journal Volume 6(2) December 2023; 53-57